2018
DOI: 10.1371/journal.pgen.1007399
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutations and somatic inactivation of TRIM28 in Wilms tumour

Abstract: Wilms tumour is a childhood tumour that arises as a consequence of somatic and rare germline mutations, the characterisation of which has refined our understanding of nephrogenesis and carcinogenesis. Here we report that germline loss of function mutations in TRIM28 predispose children to Wilms tumour. Loss of function of this transcriptional co-repressor, which has a role in nephrogenesis, has not previously been associated with cancer. Inactivation of TRIM28, either germline or somatic, occurred through inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 52 publications
3
54
0
Order By: Relevance
“…Recently, an association of germline and somatic mutations in TRIM28 with Wilms tumor development was reported by Halliday and coworkers . Their findings, namely a predominantly epithelial histology of the tumors, LOH of the TRIM28 mutation in the tumor and a lack of somatic mutations in known Wilms tumor drivers in two tumors examined, are largely in agreement with ours.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Recently, an association of germline and somatic mutations in TRIM28 with Wilms tumor development was reported by Halliday and coworkers . Their findings, namely a predominantly epithelial histology of the tumors, LOH of the TRIM28 mutation in the tumor and a lack of somatic mutations in known Wilms tumor drivers in two tumors examined, are largely in agreement with ours.…”
Section: Discussionsupporting
confidence: 90%
“…( a ) Schematic representation of the TRIM28 protein and the localization of all identified germline TRIM28 mutations. In black, variants found in this study, and in gray, variants identified by Halliday et al . The TRIM28 protein consists of a RBCC domain (amino acids 65–376), consisting of a RING‐type zinc finger (amino acids 65–121), two B‐boxes (amino acids 148–195, 204–245) and a CC‐domain amino acids (246–376), which is involved in the interaction with the KRAB domain of KRAB zinc finger proteins.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations